1996
DOI: 10.1016/s0969-2126(96)00151-7
|View full text |Cite
|
Sign up to set email alerts
|

Substrate mimicry in the active center of a mammalian α amylase: structural analysis of an enzyme–inhibitor complex

Abstract: The present analysis reveals that there are extensive interactions between the inhibitor and residues that are highly conserved in the active site of alpha-amylases; alpha-Al1 inactivates PPA through elaborate blockage of substrate-binding sites. It provides a basis to design peptide analogue inhibitors. alpha-Amylase inhibition is of interest from several points of view, for example the treatment of diabetes and for crop protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 31 publications
(86 reference statements)
9
125
0
Order By: Relevance
“…It has been suggested that peptidecarbohydrate mimicry originates in mimicry of specific chemical groups of the carbohydrate by chemical groups of the peptide (structural mimicry) (27)(28)(29). Some structural mimicry has been observed in the complexes of several mimetic proteins, e.g., in the complex of a camel heavy-chain antibody against lysozyme, where parts of some residues of the antibody mimic parts of the sugar substrate of lysozyme (30), and in the complex of porcine pancreatic ␣-amylase with the proteinaceous inhibitor, where several specific hydrogen-bonding and hydrophobic interactions with the carbohydrate substrate are mimicked by the inhibitor (31). The concept of structural mimicry is also closely related to the immune network theory of Jerne and the concept of antiidiotypic antibodies (32).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that peptidecarbohydrate mimicry originates in mimicry of specific chemical groups of the carbohydrate by chemical groups of the peptide (structural mimicry) (27)(28)(29). Some structural mimicry has been observed in the complexes of several mimetic proteins, e.g., in the complex of a camel heavy-chain antibody against lysozyme, where parts of some residues of the antibody mimic parts of the sugar substrate of lysozyme (30), and in the complex of porcine pancreatic ␣-amylase with the proteinaceous inhibitor, where several specific hydrogen-bonding and hydrophobic interactions with the carbohydrate substrate are mimicked by the inhibitor (31). The concept of structural mimicry is also closely related to the immune network theory of Jerne and the concept of antiidiotypic antibodies (32).…”
Section: Resultsmentioning
confidence: 99%
“…Structures of several u-amylases (Larson et al, 1994;Mizuno et al, 1993;Tao et al, 1989),/3-amylases (Cheong et al, 1995: Mikami et al, 1994, glucoamylase (Aleshin et al, 1992(Aleshin et al, , 1996 and complexes of these enzymes with inhibitors (Aleshin et aL, 1994;Bompard-gilles et al, 1996;Mikami et al, 1993: Stoffer et al, 1995 have provided valuable insights into their enzymatic mechanisms. However, there is no threedimensional structure of any enzyme cleaving the u-l,6-glycosidic linkage (MacGregor, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Since the patterns of inhibition of M2-4 were identical to that of M1, these other mutants were not studied further. The structure of PPA in complex with α-AI1, PDB code 1DHK (Bompard-Gilles et al, 1996) was used to construct the PPA-α-AI2 and PPA-M1 model complexes while the structure of TMA in complex with α-AI1, PDB code 1VIW (Nahoum et al, 1999) was used for modeling ZSA-α-AI2 and ZSA-M1. Alignments were adjusted so that insertions and deletions in the model proteins relative to the templates could be smoothly accommodated.…”
Section: Methodsmentioning
confidence: 99%